Accessing Difluoromethylated and Trifluoromethylated cis‐Cycloalkanes and Saturated Heterocycles: Preferential Hydrogen Addition to the Substitution Sites for Dearomatization. (8th October 2019) - Zhang, Xue; Ling, Liang; Luo, Meiming; Zeng, Xiaoming
Abstract: Reported here is a straightforward process in which a cyclic (alkyl)(amino)carbene/Rh catalyst system facilitates the preferential addition of hydrogen to the substitution sites of difluoromethylated and trifluoromethylated arenes and heteroarenes, leading to dearomative reduction. This strategy enables the diastereoselective synthesis of cis ‐difluoromethylated and cis ‐trifluoromethylated cycloalkanes and saturated heterocycles, and even allows formation of all‐ cis multi‐trifluoromethylated cyclic products with a defined equatorial orientation of the di‐ and trifluoromethyl groups. Deuterium‐labeling studies indicate that hydrogen preferentially attacks the substitution sites of planar arenes, resulting in dearomatization, possibly with heterogeneous Rh as the reactive species, followed by either reversible or irreversible hydrogen addition to the nonsubstitution sites. Abstract : Add‐ons : Die bevorzugte Addition von Wasserstoff an die Substitutionsstellen von di‐ und trifluormethylierten Arenen und Heteroarenen zur dearomatisierenden Reduktion wird beschrieben. Diese Strategie ermöglicht die diastereoselektive Synthese von cis ‐di‐ und cis‐trifluormethylierten Cycloalkanen und gesättigten Heterocyclen sowie den Aufbau von all‐ cis ‐trifluormethylierten cyclischen aliphatischen Verbindungen mit einer definierten äquatorialen Orientierung der Di‐ und Trifluormethylgruppen.